HPB P30 What is the Impact of Neoadjuvant Chemotherapy on Survival after Palliative Procedures for Pancreatic Ductal Adenocarcinoma?. (7th December 2022) - Halle-Smith, James; Roberts, Keith
Abstract: Background: Neoadjuvant chemotherapy (NAT) is increasingly offered to patients before attempting resection of pancreatic ductal adenocarcinoma (PDAC), most often to downstage locally advanced tumours but may also potentially control existing micrometastases. Unfortunately, curative resection may still not be possible in these patients. Therefore, the aim of this study was to evaluate the impact of neoadjuvant therapy on outcomes after palliative procedures for unresectable PDAC. Methods: All patients who underwent a palliative procedure for PDAC between 2014–2020 were identified from our prospectively collected and maintained institutional database. Relationships between demographics, perioperative variables, chemotherapy and postoperative survival were explored. Results: 131 patients were suitable for inclusion, of which 15 patients received neoadjuvant chemotherapy (12%). The most common reason for palliative procedure was local invasion (50%) and the most common palliative procedure was combined gastrojejunostomy and hepaticojejunostomy (55%). The NAT group were significantly younger (63 years vs. 70 years; p=0.012) but other demographic information was similar. There was no significant difference in overall survival between the NAT and no NAT groups (p=0.216). Significant independent predictors of 6-month survival were palliative chemotherapy (PC) (p<0.001) and locally advanced disease being the reason for unresectability (p=0.037), compared to liver or peritoneal metastases. PC was the only independent predictor of 12-month survival (p<0.001). Conclusions: NAT does not appear to significantly influence survival after palliative procedure for PDAC; PC remains the main factor determining survival. Low patient numbers in the NAT group reduce the statistical power of the present study, so multicentre collaborative studies are required to further investigate this important question.